Working with the Uk public sector: Sme medical device innovation and Pre-procurement - Surtees, Jennifer; Knight, Louise; Shipton, Helen (Piccola Impresa / Small Business, 2014)
Healthcare providers are under ever increasing pressure to deliver more technologically advanced care without increasing costs. Innovation is essential (Darzi, 2008), and for this healthcare providers rely on innovation within commercial companies. SMEs have an important part to play in this sector (NHS Supply Chain Parliamentary Brief, 2013). Collaboration between SME suppliers and the NHS for innovation forms the focus of this paper. We examine the academic literature on interorganizational innovation including academic insights from the areas of forward commitment procurement (Environmental Innovation Advisory Group, 2003-2008), pre-commercial procurement (Bos & Corvers, 2007), innovation and SMEs. We then explore practice, first from a policy and business sector perspective. Second, we present evidence from fifteen cases of interorganizational innovation projects involving SMEs and UK healthcare providers. Our findings show much effort is being put into creating opportunities for more interorganizational innovation of medical devices. Working across organizational boundaries presents added complexity to the innovation environment and process, and the challenge of developing high-quality cross-boundary group interaction.